2021
DOI: 10.1093/ecco-jcc/jjab011
|View full text |Cite
|
Sign up to set email alerts
|

ECCO Topical Review Optimising Reporting in Surgery, Endoscopy, and Histopathology

Abstract: Background and Aims Diagnosis and management of inflammatory bowel diseases (IBD) requires a lifelong multidisciplinary approach. The quality of medical reporting is essential in this context. The present topical review addresses the need for optimised reporting in endoscopy, surgery, and histopathology. Methods A consensus expert panel consisting of gastroenterologists, surgeons, and pathologists convened by the European Cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 188 publications
(244 reference statements)
0
37
0
Order By: Relevance
“…DCE also displays the limits of a longer examination time, the need for supplementary training, and may be considered impractical by the physicians [73]. Furthermore, a good quality surveillance with DCE demands an optimal view of the colonic mucosa [74], which is frequently affected by the quality of bowel preparation [75]. After the SCENIC consensus, two RCT and three retrospective studies observed a similar detection rate between DCE and HD-WLE [45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…DCE also displays the limits of a longer examination time, the need for supplementary training, and may be considered impractical by the physicians [73]. Furthermore, a good quality surveillance with DCE demands an optimal view of the colonic mucosa [74], which is frequently affected by the quality of bowel preparation [75]. After the SCENIC consensus, two RCT and three retrospective studies observed a similar detection rate between DCE and HD-WLE [45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in experimental settings, there can be variability between observers when subjective judgment is part of the observation, potentially leading to observer bias 44 45 The European Crohn's and Colitis Organisation has recently conducted a systematic review focused on the standardization of reporting in IBD endoscopy to improve quality and reproducibility in clinical practice and facilitate comparison of research data. 9 In the past few years, off-site revision of endoscopic videos performed by blinded experts has been recognized as an essential evaluation criterion for clinical trials, as it has been shown the additional costs are accompanied by improved result reliability and statistical efficiency. 46 Within this context, AI is widely expected to improve everyday diagnostic accuracy and reproducibility by enhancing the detection of subtle mucosal changes and standardizing lesion characterization and classification.…”
Section: Discussionmentioning
confidence: 99%
“…A minimum of two biopsies from at least five sites along the colon, including the rectum and the terminal ileum, should be obtained. 22 The features that most strongly support a diagnosis of IBD in a biopsy are basal plasmacytosis and architectural changes. Histological distinction between UC and CD in clinical practice may be difficult.…”
Section: Endoscopy and Histologymentioning
confidence: 99%
“…The histological diagnosis of UC is based on the combination of diffuse crypt architectural distortion and mucosal atrophy, and a diffuse transmucosal inflammatory infiltrate with basal plasmacytosis, with cryptitis and crypt abscesses. 22 Diagnostic features of CD are a discontinuous or focal chronic inflammation with focal crypt irregularity and granulomas. 22…”
Section: Endoscopy and Histologymentioning
confidence: 99%
See 1 more Smart Citation